DESIGN & MANUFACTURING OF WATER JAR CLEANING MACHINE - Mr. Chandragupt Parchandrao1, Mr. Ghanasham Chitari2, Rahul Satapute3, Dr. P. A. Dhawale4; Santosh Kashid (International Journal of Innovations in Engineering Research and Technology, 2022)
Jar washing machines are mainly used by several industries for quick and efficient use and for washing, bleaching, and drying jars before filling them with solution, liquids, or powders. Because jar washing is a job that permits not a single mistake in terms of hygiene and product safety. And at the same time, it demands the economical utilization of water as a valuable resource. So, the whole project is made using SS (stainless steel) frame. There is a water pump placed under the jar stand which is used to force the water from the lower level (tank) to the rinse rod. When the button is pressed the pump gets on and the water forcefully flows inside the jar through the rinse rod. And then water is then collected or thrown out by the pipe connection underneath the jar.